Ecological consequences of consecutive river damming for three groups of bioindicators - Rodríguez-Pérez, Héctor; Pannard, Alexandrine; Gorzerino, Caroline; Pellan, Laura; Massé, Stéphanie; Bouger, Guillaume; Chorin, Marion; Roussel, Jean-Marc; Piscart, Christophe (Ecological indicators, 2021)
[Display omitted] •Habitat conditions and spatial position controlled phytobenthos community.•Benthic invertebrate community was shaped by habitat conditions.•Phytoplankton community remained unchanged in spite of dams.•Riverine organism best tracked double damming. We studied three commonly used bioindicator groups: phytoplankton, phytobenthos and benthic invertebrate communities’ structure patterns in transitions between lotic and lentic habitats as consequences of two consecutive large dams constructed in the early twentieth century on the intermediate reach of a lowland river in Normandy (NW, France), the Selune. According to sampling station position along the river, including two in the two reservoir lakes, we defined three sorts of transitions, from upstream to downstream: lentic to lotic transition (hereafter len-lot), lentic to lentic transition (hereafter len-len), within the two reservoir lakes, and lentic to lotic transition (hereafter len-lot). Lot-len transition, imposed by damming, and the recovery of lotic character of the river afterward dams, promoted different diversity patterns for the studied organisms’ groups. Phytobenthos’ α diversity significantly incresed in the len-lot transition, and the highest β diversity score was observed in the lot-len. Both, habitat conditions and spatial controls drove phytobenthos community structure. Benthic invertebrate community was mainly shaped by habitat conditions. Invertebrate’s α diversity significantly changed in the lot-len and len-lot transitions, with the β diversity score being the highest in the lot-len transition. Community’s traits composition of invertebrates best fitted predictions on lotic- and lentic- type communities. Phytoplankton’s α diversity remained unchanged in the transitions and subsequently β diversity scores were low. According to the results, we proposed three classes of organisms based on their response to river damming: i) organisms indifferent or tolerant to dams effect, like phytoplankton communities in this study, that were neither hampered by changes in water flow velocity, and did not display dispersal limitation neither; ii) organisms sensitive to habitat conditions shift but not limited in their dispersal capacity by the dam, like benthic invertebrates and phytobenthos in this study. Benthic invertebrate community and phytobenthos communities differed in their response likely due to their differential dispersal capabilities and niche breadth; iii) organisms limited in their dispersal by the dam, not represented in this study. Riverine organisms best tracked transitions, while β diversity assessment revealed as the most useful metric to disentangle the relative contribution of dispersal limitation or habitat modification provoked by multiple dams.